Effect of Mixing Black Glutinous Rice and White Glutinous Rice (Oryza glutinosa) on Physicochemical Properties of Alcoholic Beverages from Tape - Elizabeth Clarabella Dupa; Thelma Jane Tuju; Tineke Marlyn Langi (Sam Ratulangi University, 2022)
This study aims to analyze the levels of alcohol, pH, total sugar, color and level of panelist preferences in alcoholic drinks from tape using ratio variations of black glutinous rice and white glutinous rice. This study used a descriptive method consisting of 3 ratio of black glutinous rice and white glutinous rice. The results of this study indicate that tape fermented drink mixed with black glutinous rice and white glutinous rice has an average range of 3.2% - 5.00% alcohol content, pH 3.40 - 3.52, total sugar 5.67°Brix – 6.90°Brix, purplish red, panelists' preference for color 4.23 (neutral) – 5.57 (slightly like), aroma 4.67 (neutral) – 5.00 (slightly like) and taste 4.10 (neutral) – 4.83 (neutral). Keywords: glutinous rice, ratio, fermentation Abstrak Penelitian ini bertujuan untuk menganalisis kadar alkohol, pH, total gula, warna dan tingkat kesukaan panelis pada minuman beralkohol dari tape menggunakan variasi perbandingan beras ketan hitam dan beras ketan putih. Peneletian ini menggunakan metode deskriptif yang terdiri dari 3 perlakuan perbandingan beras ketan hitam dan ketan putih. Hasil penelitian ini menunjukkan bahwa minuman fermentasi tape campuran beras ketan hitam dan ketan putih memiliki kisaran rata-rata kadar alkohol 3.2% - 5.00%, pH 3.40 – 3.52, total gula 5.67°Brix – 6.90°Brix, berwarna merah keunguan, tingkat kesukaan panelis terhadap warna 4.23 (netral) – 5.57 (agak suka), aroma 4.67 (netral) – 5.00 (agak suka) dan rasa 4.10 (netral) – 4.83 (netral). Kata kunci: beras ketan, perbandingan, fermentasi